Persepsi Wisatawan Terhadap Akun Media Sosial Instagram @Watuamben - Nuharani K; Dessy Rahmawati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2018)
Natural tourism destinations Watu Amben is tourist destinations which presents a panorama of the natural landscape which is located in the village of Pandeyan, district Piyungan, Bantul. One of the efforts made by the Manager of Watu Amben to introduce these tourist destinations to the public is using social media Instagram. Based on the foregoing, the researchers conducted a study with the title